Proximal venous ultrasound with risk stratification safely excludes deep venous thrombosis in emergency department routine care: an observational study - Maroan Cherkaoui; Mohammed Al-Attabi; Sara Salimi; Bader Cherkaoui; Jakob L Forberg (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Lower limb deep vein thrombosis (DVT) is common in emergency departments (EDs) and can be fatal if left untreated due to the risk of progression to pulmonary embolism (PE). In Scandinavia, DVT diagnosis typically relies on ultrasound performed outside the ED in the diagnostic departments. However, international guidelines now recommend combining limited/proximal compression ultrasound of the lower extremity PUL with risk stratification as a viable approach for diagnosing and ruling out DVT. The aim of this study was to evaluate the safety of ruling out DVT by integrating PUL with risk stratification in ED routine care. Methods This observational cohort study was conducted at the Helsingborg Hospital ED, Sweden, from April 2022 to November 2024. Adult patients with suspected DVT underwent PUL combined with risk stratification using the Wells score. Risk stratification, PUL findings, diagnosis and management plan were prospectively recorded. A 30-day follow-up was conducted to identify any subsequent DVT, PE or deaths registered as caused by PE post index visit. Patients prescribed anticoagulation following an ED-diagnosed DVT were followed up at 3 and 6 months to monitor for major bleeding events. Results A total of 560 patients were evaluated, with an overall DVT prevalence of 18.4%. Of these, 471 patients (82.5%) were managed entirely within the ED, without referral to the diagnostic department. Of the 381 patients discharged from the ED with DVT ruled out (negative PUL and low risk assessment), two were diagnosed with DVT or PE within 30 days. This resulted in a negative predictive value of 99.5% (95% CI: 98–99.9%) and a sensitivity of 97.8% (95% CI: 92.4–99.7%) for PUL combined with low-risk stratification in ruling out DVT. One of the 90 patients diagnosed with DVT in the ED and prescribed anticoagulant therapy experienced a major bleed related to an in-hospital procedure. Conclusions In this single-center ED study the combination of PUL and risk stratification in routine care was a safe and effective method for the early diagnosis and ruling out DVT. Using this approach, more than 8 out of 10 patients could be diagnosed in the ED without the need for external diagnostic support.